The physicochemical properties and stability of aspalathin in micro- and nanoencapsulated green rooibos extract formulations - Human, Chantelle (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD(FoodSc)--Stellenbosch University, 2019.